A System Dynamics Approach to Strengthening Egg Supply Chain Resilience in Banten - Saepullah, Asep; Febriani, Silvia; Ramdhani, Ade Yanyan (Tekmapro, 2025)
The growing population of Banten Province, projected to surpass 13.5 million by 2035, is expected to drive increasing demand for affordable and accessible sources of staple protein, particularly eggs. Despite producing over 315 million kilograms of eggs in 2023, the regional egg supply chain faces significant challenges, including feed price volatility, poultry mortality, inadequate infrastructure, and fragmented policy coordination. These issues contribute to supply instability and price fluctuations, which in turn affect both producers and consumers. This study employs a system dynamics approach to develop a comprehensive model of the egg supply chain resilience in Banten Province, utilizing stakeholders’ perspectives through semi-structured interviews and focus group discussions, as well as mental models derived from comprehensive literature reviews. The constructed model reveals and elucidates critical feedback mechanisms within the egg supply chain, including the hen health investment loop, price-mediated mechanisms loop, and cost-induced constraints loop. The findings highlight the critical importance of policy interventions, particularly in the areas of subsidies, infrastructure development, access to financing, and poultry health initiatives to enhance the resilience of the egg supply chain in Banten. The proposed model offers actionable insights for policymakers and establishes a conceptual framework to support future research on the egg supply chain and food system resilience in Indonesia.